(untitled) (Global Journal of Management and Business Research, 2022)
Financial reporting to external third parties is the primary document based on which, at least in theory, a company’s creditworthiness should be assessed. Income, capital, financial and sustainability performance should be understood through a thorough analysis of the financial reporting and sustainability report data. Here, we will focus exclusively on Financial reporting. As we will see, Financial reporting intended for the outside world is characterised by an information gap that tends to preserve the company’s right to information and privacy. The main objective of Financial Reporting for External Purposes is to ensure that all Financial Reporting prepared by a nation’s companies is consistent in structure and thus comparable. The spread of IAS/IFRS makes it no longer a national but a supranational objective. The significant unsolvable problem is that such financial statements, precisely in order to guarantee the privacy of certain information of a strategic nature or the disclosure of which could be detrimental to company management, are characterised by a lack of information that prevents an indepth analysis of the situation with a global company.